Implementation of Merdeka Curriculum Concept, Challenges and Benefits in Elementary School Education - Aziz, Abdul; Mukti, Husnul; Rahmawati, B. Fitri; Hadi, Yul Alfian (Sumber Belajar Sejahtera, 2025)
This study aims to analyze the concept, challenges, and benefits of implementing the independent curriculum at the elementary school level through a literature review approach. The independent curriculum is presented as a reform towards relevant and more student-centered learning, emphasizing flexibility and the development of Pancasila student profiles. Based on the literature review, it was found that there were challenges in its implementation, such as lack of teacher understanding, limited resources, and resistance to change. However, this curriculum also brings significant benefits, such as increased student learning motivation, teacher creativity, and the possibility of holistic learning outcomes. This study recommends ongoing support, such as intensive training and development of learning communities, to overcome these challenges. Therefore, the autonomous curriculum is expected to be implemented optimally, creating an adaptive and high-quality ecosystem for elementary educatio